Outsourcing Outreach: 'Counter-translation' of Outreach Activities at the Extraordinary Chambers in the Courts of Cambodia. Issue 1 (April 2022) - Kent, Alexandra
This article examines the outreach activities of the ongoing trials in the Extraordinary Chambers in the Courts of Cambodia (ECCC). The ECCC was designed to hold the leaders of Cambodia's notoriously violent Khmer Rouge regime (1975–1979) accountable. Outreach programmes have now become part of transitional justice initiatives as means to anchor their work in local and national consciousness in target countries. Using ethnographic data gathered in 2019–2020, this article explores how outreach activities have changed over time as they have become subject to new influences. I focus in particular on how some local actors have begun appropriating them in ways that represent a 'counter-translation' of the intentions originally propagated by the architects of the ECCC.